Temperature shocks and welfare costs - Michael Donadelli; Marcus Jüppner; Max Riedel; Christian Schlag (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
This paper examines the welfare implications of rising temperatures. Using a standard VAR, we empirically show that a temperature shock has a sizable, negative and statistically significant impact on TFP, output, and labor productivity. We rationalize these findings within a production economy featuring long-run temperature risk. In the model, macro-aggregates drop in response to a temperature shock, consistent with the novel evidence in the data. Such adverse effects are long-lasting. Over a 50-year horizon, a one-standard deviation temperature shock lowers both cumulative output and labor productivity growth by 1.4 percentage points. Based on the model, we also show that temperature risk is associated with non-negligible welfare costs which amount to 18.4% of the agent's lifetime utility and grow exponentially with the size of the impact of temperature on TFP. Finally, we show that faster adaptation to temperature shocks results in lower welfare costs. These welfare benefits become substantially higher in the presence of permanent improvements in the speed of adaptation.
urn:nbn:de:hebis:30:3-437499
Keywords: E30; G12; Q0; 330; temperature shocks; long-run growth; asset prices; welfare costs; adaptation